What Drives Internet Entrepreneurial Intention to Use Technology Products? An Investigation of Technology Product Imagination Disposition, Social Support, and Motivation - Huang, Tien-Chi; Wang, Yi-Jin; Lai, Hui-Min (Frontiers in Psychology, 2022)
Technological products such as computer, communication, and consumer electronic products, apps, smart wearables, and streaming services have become inseparable from people’s lives. In technological fields of practice, imagination, creativity, innovation, and entrepreneurship may influence one another. A vivid imagination can generate creativity and trigger the entrepreneurial intention to “bring new things to the market.” This study aims to understand the formation of internet entrepreneurial intention to use technology products. Drawing on social cognitive theory, this study explores and empirically tests how technology product imagination disposition and social support impact internet entrepreneurial intention to use technology products. Drawing from self-determination theory, this study proposes and examines the mediating role of intrinsic (challenge and enjoyment) and extrinsic motivation (compensation and outward motivation) in the relationship between technology product imagination disposition and internet entrepreneurial intention, as well as the relationship between social support and internet entrepreneurial intention. We conducted a survey of 568 adults in Taiwan and used partial least squares to test our hypotheses. The results show the following: (1) Technology product imagination disposition is positively associated with challenge, enjoyment, compensation, and outward motivation. (2) Social support is positively associated with challenge, enjoyment, compensation, and outward motivation. (3) Challenge, enjoyment, and outward motivation are positively associated with internet entrepreneurial intention to use technology products. (4) Technology product imagination disposition intensifies internet entrepreneurial intention to use technology products by strengthening challenge, enjoyment, and outward motivation. Social support intensifies internet entrepreneurial intention by increasing challenge, enjoyment, and outward motivation. The partial mediation model represents a significant improvement in the total effect over the direct effect. We discuss the implications of these results for research and internet entrepreneurship practices.